The antecedents and outcome of k-workers’ Leader-Member Exchange (LMX): Evidences from Chinese MNCS in China - Xiaoli, Che (2022)
Nowadays, Chinese multinational corporations (MNCs) are facing extreme pressures due to increasing costs and stiff competition from global MNCs. In order to maintain the low-cost production capability and high core competitiveness, Chinese MNCs need knowledge workers (k-workers) to support their operations. However, the work pressure faced by k-workers’ in their workplace (China), especially concerning the relationship between their supervisors, is alarming and creates a disharmonious relationship and negative attitude, which will eventually lead to a decline in their performance. Hence, in order to improve their task performance, it is necessary to improve the relationship between k-workers and their supervisors. Thus, this study aims to examine the antecedents and outcome of k-workers’ leader-member exchange (LMX) in Chinese MNCs. The study’s framework describes the antecedents (servant leadership, benevolent leadership, distributive justice, psychological empowerment) of LMX and its outcome (task performance). In addition, affective commitment and organizational citizenship behaviour (OCB) act as mediators in the relationship between LMX and task performance in this study. This study applied quantitative study using self-administered survey to collect data for the purpose of answering the research questions. To accommodate this purpose, 1132 questionnaires were distributed among Chinese MNCs and 700 were returned. Of these, 443 were useful and qualify for data analysis. The Partial Least Square Structural Equation Modelling (PLS-SEM) technique was employed for data analysis. Findings show that k-worker’s LMX is positively influenced by servant leadership, distributive justice, and psychological empowerment (only meaning and competence), and has a positive relationship with affective commitment, OCB (OCB-Individual and OCB-Organization), and task performance. Findings also show that benevolent leadership, two dimensions of psychological empowerment (self-determinant and impact) have no significant relationship with k-workers’ LMX. Additionally, the mediation effects of affective commitment, OCB (OCB-Individual and OCB-Organization) were confirmed. Hence, this study has theoretical implications and also provides practical suggestions on how to manage, motivate, and inspire Chinese k-workers, promote their task performance, and enhance the organizational performance of Chinese MNCs.